Assessment of options for small-scale groundwater irrigation in Lao PDR - Pavelic, Paul; Suhardiman, Diana; Keovilignavong, Oulavanh; Clement, Corentin; Vinckevleugel, Jordan; Bohsung, Seinab M.; Xiong, Kong; Valee, Lengya; Viossanges, Mathieu; Douangsavanh, Somphasith; Sotoukee, Touleelor; Villholth, Karen G.; et al. (Informa UK Limited, 2022)
Groundwater offers smallholder farmers in the lowlands of Lao PDR opportunities to diversify cropping beyond wet season paddy and thus enhance their livelihoods while reducing climate risks. This chapter focuses on evaluating existing and specifically developed groundwater irrigation options on the Vientiane Plain, and framing the findings around the livelihood priorities of different farming groups against a backdrop of agrarian change. Results show that cultivating a range of cash crops using shallow dugwells managed by individual farmers and deeper boreholes managed by the community can be profitable for farmers, while helping to increase the resilience of farming households’ livelihoods. Both options may also represent a viable investment option for farming households lacking access to surface water irrigation, and thus contribute to more equitable growth. The results identify drivers and conditions that incentivize and enable groundwater irrigation to generate positive development outcomes. It also highlights that farmers will not intrinsically engage in groundwater irrigation simply because a good resource is available, but instead, weighs up the pros and cons of a mix of biophysical, socioeconomic, technical, and institutional factors. Agricultural policies aiming to intensify small-scale groundwater irrigation should be cognizant of these nuances as they are critical to successful implementation and management.